The effectiveness of mindfulness training in improving the self-control of speedboat crew in Bali, Indonesia - Putu Ugram Swadharma; Alimatus Sahrah; Nur Fachmi Budi Setyawan (Jurnal Pendidikan Vokasi, 2020)
This study aims to test empirically the effectiveness of mindfulness training on improving the self-control of the crew of speedboat Company X in Bali, Indonesia. The experimental subjects in the study are 22 people who are in the sea transportation unit. They are divided into two groups, 12 of whom are in the experimental group and 10 in the control group. The data were collected by using a questionnaire with the Likert scale, consisting of 26 items with the reliability level of 0.889. The data processing used different tests. The test results of the average score of Mann-Withney of the experimental group is 16.50, which is higher than the average score of the Mann-Withney of the control group, which is 5.50, and this means that the average score of the self-control of the speedboat crew members who were treated with mindfulness training is higher than that of those who were not given mindfulness treatment. The result of U = 0.000, Z = -3.974, p (value), Asymp Sig/significance coefficient <0.05 shows that there is a significant difference in the increase of self-control between the experimental group and the control group.